Looking for ugly ducklings: The role of the stability of BrdU-antibody complex and the improved method of the detection of DNA replication - Ligasová, Anna; Konečný, Petr; Frydrych, Ivo; Koberna, Karel (PloS one, 2017)
5-Bromo-2'-deoxyuridine (BrdU) labelling and immunostaining is commonly used for the detection of DNA replication using specific antibodies. Previously, we found that these antibodies significantly differ in their affinity to BrdU. Our present data showed that one of the reasons for the differences in the replication signal is the speed of antibody dissociation. Whereas highly efficient antibodies created stable complexes with BrdU, the low efficiency antibodies were unstable. A substantial loss of the signal occurred within several minutes. The increase of the complex stability can be achieved by i) formaldehyde fixation or ii) a quick reaction with a secondary antibody. These steps allowed the same or even higher signal/background ratio to be reached as in the highly efficient antibodies. Based on our findings, we optimised an approach for the fully enzymatic detection of BrdU enabling the fast detection of replicational activity without a significant effect on the tested proteins or the fluorescence of the fluorescent proteins. The method was successfully applied for image and flow cytometry. The speed of the method is comparable to the approach based on 5-ethynyl-2'-deoxyuridine. Moreover, in the case of short labelling pulses, the optimised method is even more sensitive. The approach is also applicable for the detection of 5-trifluoromethyl-2'-deoxyuridine.
Keywords: Microscopy, Fluorescence; Humans; HeLa buňky; Bromodeoxyuridine; Cell Cycle; Copper; fluorescenční mikroskopie; A549 Cells; lidé; měď; bromodeoxyuridin; DNA Replication; Flow Cytometry; HeLa Cells; protilátky; replikace DNA; Antibodies; průtoková cytometrie; buňky A549; buněčný cyklus